Karakteristik Reproduksi dan Perbedaan Respon Fisiologis Kerbau di Lahan Basah dan Lahan Kering di Kabupaten Serang Banten - Komariah, Komariah; Santoso, K.; Siahaan, C. I. L. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
Buffalo has a higher level of adaptation than cows. The buffalo adaptation form at different locations will affect the physiological and reproduction of buffalo, so it is necessary to know buffalo adaptation on the characteristics of wetlands and dry land. This research was conducted in May to June 2017 in Kabupaten Serang, Banten. The variables observed in this research are buffalo reproduction, breeders socioeconomic, and physiological response of livestock. There were analyzed by SPSS. The results of this study indicated that buffalo reproduction characteristics in wetlands and dryland were as follows: first estrus was 22.71 ± 7.87 and 29.18 ± 11.79 months, first conception was 27.86 ± 11.43 and 32.55 ± 12.12 months, first parturition was 41.57 ± 12.33 and 26 ± 12.12 months, Calving interval was 24.10 ± 10.39 and 15.67 ± 6.55 months, calving rate was 2.36 ± 1.15 and 2.23 ± 1.20, conception period 1 year, Postpartum estroes was 6.23 ± 2.71 and 4.56 ± 2.34 months. Physiological response of livestock on dry land showed that buffalo cattle were experiencing heat stress.